Learning and Intelligent Optimization 7th International Conference, LION 7, Catania, Italy, January 7-11, 2013, Revised Selected Papers - Nicosia, Giuseppe.; Pardalos, Panos. (Lecture Notes in Computer Science, 2013)
This book constitutes the proceedings of the 7th International Conference on Learning and Optimization, LION 7, which was held in Catania, Italy, in January 2013. The 49 contributions presented in this volume were carefully reviewed and selected from 101 submissions. They explore the intersections and uncharted territories between machine learning, artificial intelligence, mathematical programming and algorithms for hard optimization problems.